Faktor Faktor Yang Berhubungan dengan Kejadian Infeksi Saluran Pernafasan Akut Berulang Pada Balita - Nofa Widyastuti; Mohammad Mirza Fauzie; Bambang Suwerda (Poltekkes Kemenkes Yogyakarta, 2011)
Acute Respiratory Infection (ARI) is the major cause of death in children under five. The occurrence of ARI among children under five in Indonesia is estimat-ed between 3 to 6 times per year. The factors suspected influencing ARI incidence are age, sex, birth weight, breast feeding, immunization status, nutri-tional status, vitamin A deficiency, contact with ARI or tuberculosis cases, antibiotics treatment, and asthma in toddlers. The study is to determine the relationship between those factors with the recurrent of ARI in children under five. This observational study used case control design and was located Alian District of Kebumen Regency. The data analysis performed by chi-square statistical test and Odds Ratio analysis at 0,05 significance level. The results showed that the risk factors for the recurrent of ARI among under five children are birth weight, breast feeding, immunization status, nutritional status, contact with people with ARI or tuberculosis, and treatment with antibiotics.